Genetic variability, character association and divergence analysis for gromorphological traits of local rice (Oryza sativa L.) germplasm in Bangladesh (Journal of the Bangladesh Agricultural University, 2020)
Rice (Oryza sativa) contributes significantly to global food security and is a major food crop for almost half of the world’s population. Fourty seven local rice germplasm were collected and grown under normal field condition to evaluate the presence of genetic diversity among them. Analysis of variance (ANOVA) showed significant differences (P ≤ 0.001) among the genotypes for all the traits studied except leaf width reflecting broad spectrum of variability which offer an ample chances for selection. The phenotypic coefficient of variation (PCV) was higher than the genotypic coefficient of variation (GCV) for most of the traits except no. of filled grains panicle-1 indicating that there was an influence of environment on majority of the studied traits. Similarly, moderate broad-sense heritability with high genetic advance as percent of mean of most of the traits such as seedling height, flag leaf area, flag leaf angle, grain length, 1000-grain weight also indicated the accumulation of additive gene effects and suggested direct selection for those characters for economic feasibility. Correlation analysis revealed significant positive and negative correlation among the traits. Principal component analysis showed that the first two principal components of the considered traits accounted for about 37.9% of the total variation and pointed out a wide variation among the genotypes. The dendrogram of cluster analysis grouped 47 rice genotypes into four clusters. Cluster II incorporated the highest number of genotypes followed by Cluster I. In terms of high yield potentiality cluster III had the highest cluster mean for rice yield, followed by cluster IV. Data from this study provide presence of sufficient genetic diversity among the traditional local rice germplasms which can be employed in future rice breeding program for either varietal improvement or developing new variety.J Bangladesh Agril Univ 18(2): 289–299, 2020https://doi.org/10.5455/JBAU.84906